HER-2/neu alterations in non-small cell lung cancer: A comprehensive evaluation by fluorescence in situ hybridization and immunohistochemistry (Annals of Medical Research, 2021)
None
Keywords: Non-Small Cell Lung Cancer; HER-2/neu; Fluorescence In Situ Hybridization; Immunohistochemistry; Gene Amplification.